The Federal Court of Canada : A History, 1875-1992 - Bushnell, Ian, 1937- (Book collections on Project MUSE., 1997)
"The Federal Court of Canada, which existed from 1875 to 1971 under the name Exchequer Court of Canada, occupies a special place in the court structure of Canada. It was founded principally to adjudicate legal disputes in which the Canadian government was involved. Since its change of name in 1971 it has become primarily an administrative appeal court dealing with the review of decisions made by federal administrative tribunals in addition to its existing jurisdictions: admiralty, intellectual property, tax, and other areas. As a federal court within the nation, its very existence has provoked discussion and debate as the various provincial court systems claim a position of primacy within our society for the adjudication of legal disputes." "Central to this history of the Federal Court is an examination of the judges who have sat on its bench, with particular focus on their views regarding the proper approach to decision making. The Federal Court of Canada is a rich resource both for those with a legal background and for those with an interest in the working and history of legal institutions."--Jacket